2020
DOI: 10.3390/radiation1010004
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Radiation Dosimetric Analysis of [68Ga]Ga-RM2: A Potent GRPR Antagonist in Prostate Carcinoma Patients

Abstract: [68Ga]Ga-RM2 is a promising innovative positron emission tomography (PET) tracer for patients with primary or metastatic prostate carcinoma. This study aims to analyze the biodistribution and radiation dosimetry of [68Ga]Ga-RM2 in five prostate cancer patients. The percentages of injected activity in the source organs and blood samples were determined. Bone marrow residence time was calculated using an indirect blood-based method. OLINDA/EXM version 2.0 (Hermes Medical Solutions, Stockholm, Sweden) was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, it has been shown that also metastases of hormone-refractory prostate carcinomas were GRPr-positive [11]. This is in line with clinical results on bombesin-based PET/CT showing promising results in patients with advanced disease in the sense of biochemical recurrence [56,57,58,59,111,112] and mCRPC patients see ▶ Fig. 1.…”
Section: Discussion On Application Of Bombesin-derivatives In Prostat...mentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, it has been shown that also metastases of hormone-refractory prostate carcinomas were GRPr-positive [11]. This is in line with clinical results on bombesin-based PET/CT showing promising results in patients with advanced disease in the sense of biochemical recurrence [56,57,58,59,111,112] and mCRPC patients see ▶ Fig. 1.…”
Section: Discussion On Application Of Bombesin-derivatives In Prostat...mentioning
confidence: 94%
“…Organ absorbed doses of [ 68 Ga]Ga-RM2 were lower than [ 68 Ga]Ga-PSMA-11, excepted for urinary bladder, pancreas and stomach wall, and comparable to other GRPr antagonists. The authors concluded that [ 68 Ga]Ga-RM2 is a safe and useful diagnostic agent for PC patients [112].…”
Section: Rm1 -Rm2mentioning
confidence: 99%
“…To our knowledge, there is no head-to-head comparison of radiolabeled NeoB and RM2 in patients and comparing results of separately performed studies is challenging due to methodological differences and differences in the patient’s characteristics. Despite this, we attempted to compare dosimetry calculations reported in two clinical studies using [ 68 Ga]Ga-NeoB and [ 68 Ga]Ga-RM2 [ 38 , 39 ]. In this comparison, the reported dose delivered to the pancreas, liver, and bladder was higher with radiolabeled NeoB vs. radiolabeled RM2.…”
Section: Discussionmentioning
confidence: 99%